Study on breastfeeding practices among rural women in the field practice areas of a tertiary care teaching hospital - Nagar, Noopur S.; Thomas, Ebbie; Nagar, Shashwat S.; Godara, Naresh R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Breastfeeding is one of the most important determinants of child survival, birth spacing, and prevention of childhood infections. The beneficial effects of breastfeeding depend on breastfeeding initiation, its duration, and the age at which the breast-fed child is weaned. Data from NFHS-4 suggest that in India, in Gujarat where only 56% of infants are exclusively breastfed and 50% of infants are initiated with breastfeeding within one hour of birth. This study was planned to identify the gaps in breastfeeding practices so that necessary interventions can be designed and thereby implemented. The objective is to study the breastfeeding practices of mothers having children below 2 years of age in the field practice areas of the medical college and to associate the findings of these practices with the socio-demographic characteristics of the population. Methods: The study conducted was a community based cross-sectional one in the six villages of RHTC of PIMSR. The study was conducted by surveying a total of 204 mothers to study their breastfeeding practices which were categorized into ‘good’ and “not so good’ practices. From this the total score was calculated and associated with socio-demographic variables. Results: Majority of the mothers were in the age group 18-22 and educated up to ‘primary’ and most of them were from social class IV and V. Only 23% of the mothers had adequate knowledge of exclusive breastfeeding. About 70% practiced both early initiation of breastfeeding and feeding colostrum whereas nearly 80% practiced exclusive breastfeeding. Conclusions: It is concluded from the study that even though the practice of breastfeeding was found quite good, the gaps in the knowledge and practice must be addressed through health education and support through peer and health groups. Documenting the success stories will go a long way for community education and behavioral change in communication at the community level for adequate breastfeeding practices.